Nasopharyngeal teratoma ('hairy polyp'), Dandy-Walker malformation, diaphragmatic hernia, and other anomalies in a female infant. - Aughton, D J (1990)
Nasopharyngeal teratomas are rare and are infrequently associated with extra-oral malformations. The case of a premature female infant with multiple congenital anomalies, including nasopharyngeal teratoma, Dandy-Walker malformation, diaphragmatic hernia, and congenital heart defect, is presented. This constellation of malformations does not appear to have been reported previously.